2020
DOI: 10.14300/mnnc.2020.15069
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical features of «Middle-Urals» variant L138ins in cystic fibr

Abstract: 1 пермский государственный медицинский университет им. Е. А. Вагнера, Российская Федерация 2 Научно-исследовательский институт пульмонологии, москва, Российская Федерация 3 медико-генетический научный центр им. академика Н. п. Бочкова, москва, Российская Федерация epiDemiological anD clinical feaTures of «miDDle-urals» VarianT L138ins in cYsTic fiBrosis shadrina V. V. 1 , Krasovsky s. a. 2 , Kondratyeva e. i. 3 , furman e. g. 1 1 e. a. Vagner perm state medical university, russian federation 2 scientific resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It was shown previously that CFTRdele2,3 variant (hg19::chr7:117138367-117159446del) has Slavic origin with the highest frequency among CF patients of 6.4% in Czechia (5.8% in Russia) [39]. Similarly, it was reported that rs397508686 (CFTR) has a lower frequency worldwide and different frequencies in Russian regions, with the highest ones in the regions of the Middle Ural; up to 3.23% frequency among patients of Ural Federal District was reported in 2019, according to the Russian CF Patients Registry [40,41].…”
Section: Discussionmentioning
confidence: 97%
“…It was shown previously that CFTRdele2,3 variant (hg19::chr7:117138367-117159446del) has Slavic origin with the highest frequency among CF patients of 6.4% in Czechia (5.8% in Russia) [39]. Similarly, it was reported that rs397508686 (CFTR) has a lower frequency worldwide and different frequencies in Russian regions, with the highest ones in the regions of the Middle Ural; up to 3.23% frequency among patients of Ural Federal District was reported in 2019, according to the Russian CF Patients Registry [40,41].…”
Section: Discussionmentioning
confidence: 97%